Fluctuations in Human Corticospinal Activity Prior to Grasp - Rao, Nishant; Parikh, Pranav J. (Frontiers in Systems Neuroscience, 2019)
Neuronal firing rate variability prior to movement onset has been found to contribute to trial-to-trial variability in primate behavior. However, in humans, whether similar mechanisms contribute to trial-to-trial behavioral variability remains unknown. We investigated the time-course of trial-to-trial variability in corticospinal excitability (CSE) using transcranial magnetic stimulation (TMS) during a self-paced reach-to-grasp task. We hypothesized that CSE variability will be modulated prior to the initiation of reach and that such a modulation would explain trial-to-trial behavioral variability. Able-bodied individuals were visually cued to plan their grip force before exertion of either 30% or 5% of their maximum pinch force capacity on an object. TMS was delivered at six time points (0.5s, 0.75s, 1s, 1.1s, 1.2s, and 1.3s) following a visual cue that instructed the force level. We first modeled the relation between CSE magnitude and its variability at rest (n=12) to study the component of CSE variability pertaining to the task but not related to changes in CSE magnitude (n=12). We found an increase in CSE variability from 1.2s to 1.3s following the visual cue at 30% but not at 5% of force. This effect was temporally dissociated from the decrease in CSE magnitude that was observed from 0.5s to 0.75s following the cue. Importantly, the increase in CSE variability explained at least ~40% of inter-individual differences in trial-to-trial variability in time to peak force rate. These results were found to be repeatable across studies and robust to different analysis methods. Our findings suggest that the neural mechanisms underlying modulation in CSE variability and CSE magnitude are distinct. Notably, the extent of modulation in variability in corticospinal system prior to grasp within individuals may explain their trial-to-trial behavioral variability.